2013
DOI: 10.1115/1.4023647
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of S Characteristics and Pressure Pulsations in a Pump-Turbine With Misaligned Guide Vanes

Abstract: Growing environmental concerns and the need for better power balancing and frequency control have increased attention in renewable energy sources such as the reversible pumpturbine which can provide both power generation and energy storage. Pump-turbine operation along the S-shaped curve can lead to difficulties in loading the rejection process with unusual increases in water pressure, which lead to machine vibrations. Pressure fluctuations are the primary reason for unstable operation of pump-turbines. Misali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Both experimental and numerical studies have revealed complex flow characters in the S-shaped region of pump-turbines. Such vortexes may partially block the flow [7,9,10], or cause stall cells to rotate in the runner channels at 50%-70% of the runner rotation frequency [5,6,8].…”
Section: Scaled Pump-turbine Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Both experimental and numerical studies have revealed complex flow characters in the S-shaped region of pump-turbines. Such vortexes may partially block the flow [7,9,10], or cause stall cells to rotate in the runner channels at 50%-70% of the runner rotation frequency [5,6,8].…”
Section: Scaled Pump-turbine Modelmentioning
confidence: 99%
“…In recent years, both experimental and modelling studies have investigated the unstable flow characteristics of pump-turbines operating in off-design conditions [5][6][7][8][9][10]. Husmatuchi et al [5,6] experimentally investigated pressure fluctuations in the gap between the guide vanes and runner.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid the operating point from the 'S' characteristic area, Kuwabara et al proposed a curved closing scheme that could effectively decrease the water-hammer pressure [12]. Additionally, appropriate two-phase closing scheme [13,14] and misaligned guide-vane method [15][16][17] also have been applied to control the fluctuation of PSHU. Three-phase valve-closing and curved closing scheme exerted high demands on the governor servomotor, which are difficult to realize in PSP.…”
Section: Of 26mentioning
confidence: 99%
“…Three-phase valve-closing and curved closing scheme exerted high demands on the governor servomotor, which are difficult to realize in PSP. Meantime, misaligned guide-vane method can significantly increase the pulsating pressure and the runner radial forces during start-up process of PSHU [17]. Therefore, the optimal closing schemes are required to realize optimal coordinated operation of PSP and new energy generation technologies based on deeply analysis of operational mechanism and flow characteristics of PSHU.…”
Section: Of 26mentioning
confidence: 99%
“…What brought about this S-Shaped characteristic appear to be in relation with the development of vortexes in the pump-turbine partly blocking the flow [4][5][6]. Established from Some studies indicate that the advancement of stall cells gyrating in the runner channels at 5070% of the rotational frequency of the runner [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%